(untitled) (Annals of Medical Research, 2021)
Aim: Bone-borne rapid maxillary expander (RME) is one of the latest expander designs being used for skeletal expansion by applying forces through palatal mini-screws. The purpose of this retrospective study was to evaluate soft tissue facial changes following RME using 3D stereophotogrammetry. Materials and Methods: A total of 15 subjects (6 males and 9 females) with a mean age of 12.1±1.4 years who underwent upper arch expansion using bone-borne RME as a component of their orthodontic therapy were recruited in this retrospective study. 3D facial images (3dMD Ltd, Atlanta, Ga) generating 3D soft tissue meshes before expansion (T0), immediately after expansion (T1), and after a 3-month retention phase (T2) were used to capture facial scans of 15 subjects. Based on twenty-three landmarks, 10 linear measurements were made from each of 3D images. Comparisons of measurements at 3 different times were evaluated with one-way Repeated Measures Analysis of Variance (p < 0.05). Results: Statistically significant changes were observed in the mouth (chr-chl) and nasal (alr-all) width in T0-T1 and T0-T2. No significant differences were found in the upper and lower face heights, total face height, upper and lower lip heights, upper and lower vermillion heights and intercanthal width. Conclusion: Significant increases in mouth and nose width were obtained by bone-borne RME. These changes remained stable for 3 months. 3D stereophotogrammetric facial imaging method is an easy and non-invasive method that can be used to analyze the changes of facial soft tissues after RME treatment.